Promoting a “Unity of Feeling”: The Rebellions of 1837/1838 and the Peterborough Region - Carter-Edwards, Dennis (Ontario History, 2009)
The Rebellions of 1837 and subsequent border raids by American sympathizers prompted colonial officials to call out local militia units for extended duty. The threat of armed conflict and political uncertainty heightened the underlying social, class and ethno-cultural tensions that existed in Upper Canadian society. This article examines the impact of the Rebellions in the Peterborough area, particularly among the Irish settlers, and how these tensions were manifested in the actions of the 7th Provisional Battalion during the period they were stationed in Peterborough.